SISTEM INFORMASI GEOGRAFIS WILAYAH RAWAN BANJIR DI KOTA PEKANBARU - luluk elvitaria elvitaria; Miftahul Khasani (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2019)
Based on the geographical location of Pekanbaru City is one of the areas included in flood-prone areas, even said that the city of Pekanbaru is included in the red zone related to flooding, seeing from the majority of the existing area is the rawah and river banks. The National Flood Mitigation Agency (BNPB) noted that the city of Pekanbaru is one of the flood-prone cities on the island of Sumatra. In addition to determining flood-prone areas for the Regional BPBD Office in Pekanbaru City, the community also wants to know the location that often floods and determine the long-term rain intensity capacity that will cause flooding, so that it does not hinder the daily activities. To deal with this problem, a Geographical Information System needs to be developed that can determine areas that often occur in natural flooding. Geographical information systems are expected to be able to assist the BPBD Office in managing flood data that has occurred in the city of Pekanbaru, and help provide information about floods that are needed by the community to anticipate further flood events.